DUTY TO ISPECT GOODS ACCORDING TO CISG (VIENNA CONVENTION) - Ratko Brnabić (Zbornik Radova Pravnog Fakulteta u Splitu, 2008)
The CISG requires buyers to inspect goods, and provide adequate and timely notice, with respect to any defects in the seller’s performance and preserve the goods in the event the buyer elects to reject the seller’s tender. These obligations are set forth in Articles 38, 39, 44 and 86. The initial obligation of all buyers is the duty of inspection. Article 38 provides that the buyer “must examine the goods, or cause them to be examined, within as short a period as is practicable in the circumstances.” Special rules apply in the event the contract involves the carriage of goods or their redirection in transit. Examination may be deferred until after the goods arrive at their destination in the event the contract involves carriage. By contrast, examination of the goods may be deferred until after their arrival at their ultimate destination in the event they have been redirected in transit or re-dispatched by the buyer. However, the inspection may be deferred under these circumstances only if the redirection or re-dispatch occurred without a “reasonable opportunity” for examination. In addition, the buyer must demonstrate that the seller knew or should have known of the possibility of such redirection or re-dispatch at the time of the conclusion of the contract. The failure to comply with the provisions of Article 38 deprives the buyer of the right to rely upon the defense of nonconformity of the goods in a future dispute with the seller.